The Problems of Enforcement of Citizens' Constitutional Rights and Liberties in Forensic Practice - S. A. Smirnova; O. V. Miklyaeva (Теория и практика судебной экспертизы, 2017)
Various problems of law enforcement practice, e.g. ensuring an adequate scientific level of forensic assistance in criminal proceedings, regulations governing forensic practice, and methodological support for forensic examinations, are examined from the perspective of basic constitutional principles. The authors propose ways to improve current legislation on forensic practice in the Russian Federation.